Pengaruh Pemberian Ekstrak Etanol Brokoli (Brassica oleracea) terhadap Kadar SGOT dan SGPT Tikus Wistar yang Diinduksi DMBA (The Effect of Ethanolic Extract of Broccoli (Brassica oleracea) on SGOT and SGPT of Wistar Rats Induced by DMBA) - Rizka Nuzula Wardani; Elly Nurus Sakinah; Yudha Nurdian (UPT Percetakan dan Penerbitan Universitas Jember, 2016)
DMBA is a product of incomplete burning which can cause free radicals in human. The metabolism of DMBA by Cytochrome P450 in liver causes hepatocyte DNA damage and decrease endogenous antioxidant. Broccoli contains flavonoid which can act as an antioxidant by inhibiting formation of free radicals through hydrogen atom donation to free radicals. This research aimed to analyze the effect of ethanolic extract of broccoli on SGOT and SGPT of wistar rats induced by DMBA. This research used 24 rats divided into six groups: control group, negative control group, and four treatment groups with broccoli ethanolic extract of 250 mg/kgBW, 500 mg/kgBW, 1000 mg/kgBW, and 2000 mg/kgBW for 7 days. The SGOT and SGPT levels of control group were 70,36 U/L and 33,97 U/L; negative control group 107,16 U/L and 56,21 U/L; the first treatment 101,50 U/L and 49,33 U/L; the second treatment 85,32 U/L and 43,67 U/L; the third treatment 84,11 U/L and 40,84 U/L; and the fourth treatment 81,28 U/L and 35,18 U/L. The result of One Way Annova test for SGOT was p=0,012 while SGPT was p=0,003. In this study, ethanolic extract of broccoli could protect hepatocyte by decreasing SGOT and SGPT levels. Keywords: ethanolic extract of broccoli, SGOT and SGPT levels, DMBA